Frequency and Characteristics Associated With Exposure to Tobacco Direct Mail Marketing and Its Prospective Effect on Smoking Behaviors Among Young Adults From the US Midwest - Choi, Kelvin (American Public Health Association, 2014)
Objectives. We examined the exposure to tobacco direct mail marketing and its effect on subsequent smoking behaviors in a US Midwest regional cohort of young adults. Methods. Data were collected from 2622 young adults (mean age = 24 years) in 2010 to 2011 (baseline) and 2011 to 2012 (follow-up). We collected information on demographics, tobacco use, and exposure to tobacco direct mail materials in the previous 6 months at baseline. Smoking behaviors were reassessed at follow-up. We investigated the characteristics associated with receiving these materials at baseline, and the associations between receiving cigarette coupons in the mail at baseline and smoking behaviors at follow-up. Results. Thirteen percent of participants reported receiving tobacco direct mail materials in the previous 6 months. Receipt of these materials was associated with age, education, and tobacco use (P < .05). Among those who received these materials, 77% and 56% reported receiving coupons for cigarettes and other tobacco products, respectively. Among baseline nonsmokers and ex-smokers, receiving coupons was associated with becoming current smokers at follow-up (P < .05). Among baseline current smokers, receiving coupons was associated with lower likelihood of smoking cessation at follow-up (P < .05). Conclusions. Tobacco direct mail marketing promoted and sustained smoking behaviors among US Midwest young adults. Regulating this marketing strategy might reduce the prevalence of smoking in this population.